“Phyto-Chemical and Antiviral Study on Glycyrrhiza Glabra, Phyllanthus Amarus and Solanum Nigrum Against Hepatitis C Virus” - Ravichandran, Jayashree; Rengachari, Nanthini; Muruganantham, Swetha; Aruljothi, Mugunthan; Manickam, Elanchezhiyan (European Journal of Applied Sciences, 2022)
Hepatitis C virus (HCV) is a serious public health concern that affects millions of people worldwide, causing liver cirrhosis and Hepatocellular carcinoma (HCC). While there are no effective anti-HCV vaccines, the availability of potent anti-HCV drugs has streamlined the management of viral hepatitis and its complications. There are currently many DAA’s available to help keep HCV infections under control. DAA’s, on the other hand, are known to cause untoward side effects in addition to being expensive. Furthermore, DAA’s role in treating drug-resistant HCV is known to be difficult. These facts necessitate the development of newer anti-HCV drugs, which are currently being pursued. Looking for alternative drugs from natural resources is one approach to discovering novel anti-HCV drugs. In this study, we evaluated the anti-HCV and phytochemical properties of extracts derived from G. glabra, S. nigrum and P. amarus. The anti-HCV activity of plant extracts was tested on the FL-J6-JFH replicon system and found a strong anti-HCV activity elicited by S. nigrum aqueous extract (IC50-95.8µg/ml) followed by G. glabra methanolic extracts (IC50-97µg/ml). All plants had comparable levels of flavonoids, tannins, phenols, carbohydrates, proteins, and lipids, according to phytochemical analysis. Our study disclosed a novel plant i.e., S. nigrum as an effective drug against HCV.